2002
DOI: 10.1063/1.1479478
|View full text |Cite
|
Sign up to set email alerts
|

Two different behavior patterns of photoluminescence depending on Mg doping rate in p-type GaN epilayers

Abstract: Mg-doped p-type GaN epilayers grown by metalorganic chemical vapor deposition exhibit two different types of photoluminescence (PL) characteristics depending on Mg doping rate; the existence of critical Mg concentration is found where both electrical and optical characteristics show an abrupt change in their behavior. In samples with relatively low Mg concentration, a band edge emission, a peak associated with shallow donor-acceptor pair recombination, and a 2.8 eV blue band emission appear in the PL spectrum.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…[15][16][17] It is reported that a thermal annealing can make H atoms change into various states, and the concentration for each state is determined by the thermal equilibrium and affected by annealing temperature. [18] The improvement of p-type quality means that the H + concentration in p-type layer decreases with annealing temperature increasing in our experiment. With the increase of annealing temperature, more and more Mg acceptors are activated by thermal annealing.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…[15][16][17] It is reported that a thermal annealing can make H atoms change into various states, and the concentration for each state is determined by the thermal equilibrium and affected by annealing temperature. [18] The improvement of p-type quality means that the H + concentration in p-type layer decreases with annealing temperature increasing in our experiment. With the increase of annealing temperature, more and more Mg acceptors are activated by thermal annealing.…”
Section: Resultsmentioning
confidence: 53%
“…In the annealing process, the H atom can change into various states and in these states of the H atom the H − can combine and change the donors' state. [18] The effect of annealing on the compensation donors also relates to the H state changing in the annealing process, but more work needs to be done to confirm this point.…”
Section: Resultsmentioning
confidence: 99%
“…Similar blue emission has been observed and well-studied for Mg 2+ -and Zn 2+ -doped GaN in films. [29][30][31] These peaks are attributed to donor-acceptor pair recombination, preferentially from the conduction band to the shallow acceptor states (ca. 0.5 eV above the valence band) created by the incorporation of Mg 2+ or Zn 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…For epitaxial GaAs bandedge luminescence is also quenched with oxygen doping to 10 18 cm −3 in favour of near mid-gap deep level trap-related PL peaks [120]. For GaN, heavy Mg doping also results in the quenching of band-edge luminescence in favour of a blue luminescence band possibly related to deep level acceptor states [121], while for epitaxial CdTe deep level emissions with 14 meV FWHM have been observed (much sharper than any of the InN emissions observed to date) but only for samples greater than 3 µm in thickness [122]. Again no band-edge luminescence was observed.…”
Section: Trapping Levelsmentioning
confidence: 96%